Philosophy of Ch. Chhotu Ram to upliftment the Rural Society - Devi, Dharshana (Innovative Research Thoughts, 2017)
Before analysing and writing about a person, his background, his past history, his family, neighbourhood, environment, circumstances, actions, feelings, thoughts and dreams are considered. it is a fact that present is connected to the past in one way or the other. Ch.Chhotu Ram was so important personality that he represented in himself an institution an embodiment of thoughts, a popular leader pivot of the future of peasantry society of Punjab before independence and trust worthy to the core. He gained popularity not only Hindu peasantry Society, but also muslim and down trodden people in a short time. Being Minister without any vested interest, smiling without getting tired, thought of the upliftment of the peasantry society and its rural poor citizen.